The Challenges of Dialysis in Systemic Sclerosis: Between the Devil and the Deep Blue Sea?. (17th September 2012) - Brown, N.; Summers, A.; Venning, M. C.; Bruce, I. N.
Abstract : We present the case of a patient with systemic sclerosis (SSc) and end stage renal disease (ESRD) who experienced complications of both peritoneal and haemodialysis. We review previously reported outcomes of patients with systemic sclerosis on dialysis and discuss potential shared mechanisms in both the disease pathogenesis and dialysis-related complications, particularly with regards to encapsulating peritoneal sclerosis (EPS).